Determination of GHB in human hair by HPLC‐MS/MS: Development and validation of a method and application to a study group and three possible single exposure cases. Issue 5 (19th June 2014) - Bertol, Elisabetta; Mari, Francesco; Vaiano, Fabio; Romano, Guido; Zaami, Simona; Baglìo, Giovanni; Busardò, Francesco Paolo
<x xml:space="preserve">Abstract</x> Gamma‐hydroxybutyrate (GHB) over the last two decades has generated increased notoriety as a euphoric and disinhibiting drug of abuse in cases of drug‐related sexual assault and for this reason it is considered a 'date rape' drug. The first aim of this paper was to develop and fully validate a method for the detection of GHB in human hair by high performance liquid chromatography‐tandem mass spectrometry (HPLC‐MS/MS) after liquid‐liquid extraction (LLE). The second aim was the application of the method to hair samples of 30 GHB‐free users in order to determine the basal level. The results obtained showed no significant differences in endogenous concentrations (p = 0.556) between hair samples of the three groups (black, blonde, and dyed hair) and the age and sex of the subjects did not affect the endogenous levels. Another 12 healthy volunteers, with no previous history of GHB use, were selected and a single dose (25 mg/Kg) was orally administered to all of them and hair samples were collected before the administration of the single dose and other two samples were collected one month and two months later, respectively. The segmental analysis of the latter two samples allowed us to calculate two ratios: 4.45:1 (95% C.I. 3.52–5.63) and 3.35:1 (95% C.I. 2.14–5.18), respectively, which can be recommended as reasonable values for a positive identification of GHB intake. Finally the method was applied to three real cases where a GHB single exposure probably occurred. Copyright © 2014 John Wiley & Sons, Ltd.